(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In order to thoroughly study the language units of foreign languages selected for the implementation of work in the field of translation, information about lexical, grammatical and stylistic transformations is highlighted through examples. Also, during the study of this scientific work, great importance is attached to the process of linguistic and cultural analysis. In order to understand the difference between cultures, it is necessary to understand and study the mentality of the people in the original language of the text.